Kematangan Emosi dan Religiusitas Terhadap Kecenderungan Agresi Pada Siswa - Maharani, Putri; Laksmiwati, Hermien (Universitas Negeri Surabaya, 2017)
The purpose of this research was to determine the correlation between emotional maturity and religiosity with aggressive tendency among students. This research used quantitative research method. The population was Â grade 10 Â students ofÂ SMA